Permitted and prohibited desires : mothers, comics, and censorship in Japan - Allison, Anne, 1950- (University of California Press, 2000)
This provocative study of gender and sexuality in contemporary Japan investigates elements of Japanese popular culture including erotic comic books, stories of mother-son incest, lunchboxes - or obentos - that mothers ritualistically prepare for schoolchildren, and children's cartoons. It provides an analysis of how sexuality, dominance, and desire are reproduced and enacted in late-capitalistic Japan.